English language teachers' differential treatment of the good, average and slow learners and their answering moves an interactional analysis - Florendo, Thelma E. 1930-
The main purpose of the study is to identify and describe a pattern of differential teaching towards the good, the average, and the slow English language learners and their response to such teaching in the Silliman University Elementary School.